2015
DOI: 10.1039/c4tc02378a
|View full text |Cite
|
Sign up to set email alerts
|

The role of nanoporosity on the local piezo and ferroelectric properties of lead titanate thin films

Abstract: Nanoporous and dense ferroelectric PbTiO 3 thin films are prepared by a modified solgel process. The presence of nanoporosity, with ~ 50 nm pore size formed using a block polymer as a structure-directing agent, markedly affects the microstructure, crystallization and ferroelectric film´s properties. The crystallization of the tetragonal phase is enhanced in nanoporous films. It is suggested that the decomposition of the block-copolymer in porous films triggers the crystallization of the perovskite phase at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 19 publications
(29 reference statements)
4
38
1
Order By: Relevance
“…By controlling porosity, pore size, shape, and interconnectivity, the functional properties (dielectric, ferroelectric, piezoelectric, etc.) of ferroelectric ceramics can be tailored . Very often porosity is introduced in the bulk materials by addition of a pore‐forming agent; in the case of PZT materials it is possible to take advantage of the volume increase during the perovskitic phase formation to keep a consistent amount of porosity in the sintered sample by heating directly the pressed homogeneous mixture of the starting oxides (reaction sintering).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…By controlling porosity, pore size, shape, and interconnectivity, the functional properties (dielectric, ferroelectric, piezoelectric, etc.) of ferroelectric ceramics can be tailored . Very often porosity is introduced in the bulk materials by addition of a pore‐forming agent; in the case of PZT materials it is possible to take advantage of the volume increase during the perovskitic phase formation to keep a consistent amount of porosity in the sintered sample by heating directly the pressed homogeneous mixture of the starting oxides (reaction sintering).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the experimental results have shown that for a porosity level around 20%, an optimum compromise between a reasonable permittivity decrease down to hundreds while maintaining a tunability similar as in the dense material, can be achieved . In some specific configurations, porosity had even a positive role in enhancing ferroelectric switching, due to the field concentration in ferroelectric regions, thus stimulating the polarization reversal at smaller coercive fields than in the dense material . Motivated by these results, the objective of this study is to investigate the dielectric, ferroelectric, and structural properties of porous PZTN ceramics produced by reaction sintering, with porosity in the range 20%‐30%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have proved the piezo-and ferro-electric properties at the nanoscale of porous barium titanate (BaTiO 3 ) and lead titanate (PbTiO 3 ) thin films. 17,18 The main difficulty in this work is the control of the porosity order during the thermal treatment needed to crystalize the tetragonal phase. We have also observed that porosity induces the crystallization of tetragonal PbTiO 3 at a temperature lower than that of the dense counterparts.…”
Section: Introductionmentioning
confidence: 99%